Bioavailability of acalabrutinib suspension delivered via nasogastric tube in the presence or absence of a proton pump inhibitor in healthy subjects. Issue 10 (25th May 2022) - Sharma, Shringi; Pepin, Xavier; Cheung, Jean; Zheng, Lianqing; Wei, Hua; Townsley, Danielle; Han, David; Majewski, Michal; Ware, Joseph A.; Mann, James; Munugalavadla, Veerendra; Sheridan, Louise; et al.
Abstract : Aims: Acalabrutinib, a selective Bruton tyrosine kinase inhibitor, is approved for the treatment of mantle cell lymphoma and chronic lymphocytic leukaemia. Many critically ill patients are unable to swallow and need oral medications to be delivered via a nasogastric (NG) tube. Furthermore, critically ill patients are typically administered proton‐pump inhibitors (PPIs) to prevent stress ulcers. Concomitant administration with PPIs reduces acalabrutinib exposure and is not currently recommended. To evaluate acalabrutinib in subjects co‐administered with PPIs who require NG delivery, a phase 1, open‐label, randomized, crossover, single‐dose study was conducted in healthy subjects. Methods: The study assessed the relative bioavailability of an acalabrutinib suspension—in regular, degassed Coca‐Cola—administered via NG tube (Acala‐NG) versus the pharmacokinetics (PK) of an acalabrutinib capsule administered orally with water. In addition, the PPI effect was evaluated by comparing the PK following Acala‐NG in the presence or absence of rabeprazole. Results: Exposure of acalabrutinib and its active metabolite (ACP‐5862) were comparable following administration of Acala‐NG versus the oral capsule (Geo mean ratio, % ref [90% confidence interval, CI]: acalabrutinib AUCinf : 103 [93‐113]; C max : 144 [120‐173]). In addition, exposure was similar following administration of Acala‐NG with and without a PPI (Geo mean ratio, % ref [90% CI]: acalabrutinib AUCinf : 105 [79‐138]; C max : 95 [66‐137]). No safety or tolerability concerns were observed, and all adverse events were mild and resolved without treatment. Conclusions: Acala‐NG with or without a PPI is safe and well‐tolerated without impeding bioavailability.